One-stage tubeless percutaneous nephrolithotomy for asymptomatic calculous pyonephrosis - Guo, Shijie; Zhang, Xicai; Li, Fengyue; Sun, Chunyue; Zhang, Yonghe; Cao, Xiande (BMC urology, 2022)
In recent years, the safety and effectiveness of one-stage percutaneous nephrolithotomy (PCNL) for the treatment of calculous pyonephrosis have been proven. In order to further reduce postoperative pain and hospital stay, we first proposed and practiced the idea of one-stage tubeless percutaneous nephrolithotomy for calculous pyonephrosis. A retrospective analysis was performed of case data of 30 patients with asymptomatic calculous pyonephrosis treated in our center with one-stage PCNL from January 2016 to January 2021. Patients were routinely given 20 mg of furosemide and 10 mg of dexamethasone sodium phosphate injection intravenously at the beginning of anesthesia. Among them, 27 patients successfully underwent one-stage tubeless percutaneous nephrolithotomy, while 3 cases were given indwelling nephrostomy tubes because of proposed second-stage surgery or the number of channels was greater than or equal to 3. All patients were operated on by the same surgeon. Preoperatively, 11 of 30 patients (8 men and 22 women) had positive urine bacterial cultures, and all were given appropriate antibiotics based on drug sensitivity tests. All patients completed the surgery successfully. The mean operative time was 66.6 ± 34.7 min, the mean estimated blood loss was 16.67 ± 14.34 mL and the mean postoperative hospital stay was 5.0 ± 3.1 days. The mean postoperative hospital stay was 4.6 ± 2.5 days among the 27 patients with one-stage tubeless percutaneous nephrolithotomy. Of the 3 patients with postoperative fever, 2 had the tubeless technique applied. One patient with 3 channels was given renal artery interventional embolization for control of postoperative bleeding. None of the 30 patients included in the study developed sepsis. The final stone-free rate was 93.3% (28/30) on repeat computed tomography at 1 month postoperatively. The final stone-free rate was 92.6% in the 27 patients undergoing one-stage tubeless percutaneous nephrolithotomy (25/27). One-stage tubeless PCNL is an available and safe option in carefully evaluated and selected calculous pyonephrosis patients.